Mémoires de Lorenzo D'Aponte : Poète Vénitien: Collaborateur de Mozart - Da Ponte, Lorenzo 1749-1838; De la Chavanne, M. C. D. (Paris Pagnerre, 1860)
Lorenzo Da Ponte is known not only for having written the librettos for several of Mozart's operas, but also for his many professions. In this memoir, he recounts his eventful adventures, from Venice to New York, via Vienna and London. Here, Lorenzo Da Ponte delivers a captivating account of his life and his encounters with the great musical and cultural figures of his time. (Translated with Deepl.com)
Keywords: 18th Century (1701-1800); 19th Century (1801-1900); Poet; Biography; Travel